2008
DOI: 10.1016/j.jdeveco.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Can micro-credit bring development?

Abstract: We examine the long-run effects of micro-credit on development in an occupational choice model similar to Banerjee and Newman (JPE, 1993). Micro-credit is modeled as a pure improvement in the credit market that opens up self-employment options to some agents who otherwise could only work for wages or subsist. Micro-credit can either raise or lower long-run GDP, since it can lower use of both subsistence and full-scale industrial technologies. It typically lowers long-run inequality and poverty, by making subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
99
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 21 publications
8
99
1
Order By: Relevance
“…Groups play a role that depends on meeting costs and time use introduced in the next two sections. 6 Other than the above mentioned papers, our paper is also broadly related to the theoretical literature in microfinance that has emerged in the light of the Grameen Bank of Bangladesh abandoning explicit joint liability and switching to the Grameen II model, focusing on aspects other than joint liability, such as sequential lending (e.g., Chowdhury, 2005), frequent repayment (Jain and Mansuri, 2003;Fischer and Ghatak, 2010), exploring more general mechanisms than joint liability (e.g., La↵ont and Rey, 2003), and exploring market and general equilibrium (Ahlin and Jiang, 2008;McIntosh and Wydick, 2005;de Quidt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Groups play a role that depends on meeting costs and time use introduced in the next two sections. 6 Other than the above mentioned papers, our paper is also broadly related to the theoretical literature in microfinance that has emerged in the light of the Grameen Bank of Bangladesh abandoning explicit joint liability and switching to the Grameen II model, focusing on aspects other than joint liability, such as sequential lending (e.g., Chowdhury, 2005), frequent repayment (Jain and Mansuri, 2003;Fischer and Ghatak, 2010), exploring more general mechanisms than joint liability (e.g., La↵ont and Rey, 2003), and exploring market and general equilibrium (Ahlin and Jiang, 2008;McIntosh and Wydick, 2005;de Quidt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As such, microfinance enables the poor to increase their income, consumption, and productivity, which contributes to lowering inequality. Ahlin and Jiang (2008) describe a model in which the adoption of microfinance is considered financial development and show that microfinance decreases inequality.…”
Section: Introductionmentioning
confidence: 99%
“…Literature research has revealed that the wider consequences of microcredit on society are poorly studied and understood (Develtere and Huybrechts 2005;Perry 2002). Research on the longer-term effects of microcredit is in its infancy (Ahlin and Jiang 2008;Khandker 2005;Moll 2005). Perry (2002:32) summarizes that "'impact' studies reign over 'institutional' studies that examine broader social and economic changes".…”
Section: Introductionmentioning
confidence: 99%